Silent new ischemic lesions after index stroke and the risk of future clinical recurrent stroke. (19th January 2016) - Kang, Dong-Wha; Han, Moon-Ku; Kim, Hye-Jin; Sohn, Hoyon; Kim, Bum Joon; Kwon, Sun U.; Kim, Jong S.; Warach, Steven
Abstract : Objective: To test whether a silent new ischemic lesion (SNIL) on MRI after stroke predicted future recurrent ischemic stroke or vascular events. Methods: In this prospective study, we analyzed data from patients presenting with acute ischemic stroke who underwent MRI <24 hours and 5 and 30 days after symptom onset. The presence of a SNIL at 5 (5D-SNIL) and 30 (30D-SNIL) days was determined on diffusion-weighted and fluid-attenuated inversion recovery images. Patients were contacted every 3–6 months to identify recurrent clinical events. The log-rank test and Cox proportional hazard model were used to estimate the hazard ratio of recurrent ischemic stroke and composites of recurrent ischemic stroke, transient ischemic attack, acute coronary syndrome, and vascular death. Results: The 5D- and 30D-SNILs were found in 24.4% (66/270) and 7.4% (19/256) of patients. During the 5-year follow-up, clinical events were observed in 42 patients (15.6%). The 5D- and 30D-SNIL independently predicted recurrent ischemic stroke (hazard ratio [95% confidence interval] 2.9 [1.3–6.4] and 9.6 [4.1–22.1], respectively) and composite vascular events (2.4 [1.3–4.5] and 6.1 [3.1–12.4], respectively). Conclusions: Patients with a SNIL within the first few weeks after index stroke have an increased risk of recurrent ischemic stroke or vascular events. The presence of a SNIL on MRI could serve as a surrogate endpoint for clinical recurrence in secondary prevention clinical trials.